Draft Ministerial text for the Cancun session is leaked - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The draft Cancun Ministerial text was leaked on July 18th 2003. It leaves wide...